Effects of long spray-chilling on water pocket development in ribeyes. (July 2017) - de Mello, A.S.; Ringkob, T.P.; Yeh, Y.
Abstract: Water Pocket (WP) is a defect on beef that may lead to significant economic losses. Our hypothesis is that longer spray-chilling time increases WP incidence on ribeyes ( M. longissimus thoracis ). Ribeyes (28, 801) were visually evaluated for the presence of WP after 24 or 72 h of spray chilling. Additionally, 252 beef sides were evaluated prior to chilling to predict WP development after 24 h of spray chilling. Also, the 12th rib fat thickness was measured on 313 sides and the sides were assigned to two categories of WP or no WP to evaluate fat thickness as an indicator for WP. Subcutaneous fat softness is not related to WP development, longer spray-chilling does not increase the incidence of WP in ribeyes, and thinner subcutaneous fat is an indicator for WP development. Highlights: Automated hide pulling mechanisms detach subcutaneous fat from the epimysium and affect its thickness. Water pocket is a common defect on beef carcasses processed with hide pullers and spray-chilled. Longer spray chilling does not increase the incidence of water pockets in ribeyes. Thinner subcutaneous fat is an indicator of WP pocket development.